Effect of FRP Sheets Length on the Ultimate Loading Capacity of CFRP and GFRP Strengthened Hollow-Core Slabs by the Finite Element Method - et. al., Muhammed Maleknia, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Numerous studies have been conducted on the strengthening of reinforced concrete building components such as beams and columns, which are under shear, bending, or torsion, using the fiber-reinforced polymer (FRP) in the form of external coverage. However, a few studies have addressed the strengthening of concrete slabs, especially hollow-core slabs. Moreover, the calculation of the optimal fiber length to reduce the cost and time spent on project implementation is a basic issue. Therefore, this study scrutinized the effect of FRP sheets length on the ultimate loading capacity of CFRP and GFRP strengthened hollow-core slabs by the finite element method. In this regard, the concrete hollow-core slab was modeled in ANSYS software and compared with the available experimental model for verification. Then, the bending reinforcement of the aforementioned slab by CFRP and GFRP fibers was investigated at different distances from the face of support. These changes were inserted into hollow-core slabs with lengths of 1.5 m and 9 m. It was indicated that in the 1.5 m slab, the optimal CFRP fiber length was about one-tenth from the face of support and this value was one-fifth for GFRP fibers. Also, For the 9 m hollow-core slab, the optimal CFRP fiber length was about one-fifth from the face of support and this value was one-third for GFRP fibers. Finally, it was concluded that FPR sheet installation in lengths more than the optimal length has no impact on the final capacity of the mentioned slabs. Therefore, it is better to install FRP sheets in the calculated distances (optimal fiber length) to save time and costs.